The Effectiveness of Expressive Writing on Psychological Well-Being in Islamic Boarding School Students (Santri) - Dewi, Apriliani Rosita; Purwandari, Eny (Universitas Muhammadiyah Surakarta, 2025)
Psychological well-being represents an essential dimension of human quality of life, encompassing autonomy, personal growth, positive relationships, purpose in life, and self-acceptance (Ryff, 1989; Ryff, 2013). Globally, disparities in well-being remain substantial. According to the World Happiness Report 2024, Finland ranked highest with a score of 7.741, while Afghanistan was lowest with 1.721 (Helliwell et al., 2024). Concurrently, the World Health Organization (WHO, 2022) reported that one in eight individuals suffers from a mental disorder. In Indonesia, the Indonesian National Adolescent Mental Health Survey (I-NAMHS, 2022) revealed that one in three adolescents (34.9%), equivalent to approximately 15.5 million youths, experienced a mental health disorder within the past year (Center for Reproductive Health, University of Queensland, & Johns Hopkins Bloomberg School of Public Health, 2022).Adolescence is a critical developmental stage characterized by identity-seeking, emotional fluctuation, and heightened vulnerability to stress (Erikson in Danyalin & Tantiani, 2022; Leuwol, Jamin, & Ayu, 2023). Effective psychosocial support during this phase is essential, particularly in institutional settings such as Islamic boarding schools (pesantren), which play a major role in shaping adolescent identity in Indonesia. Pesantren emphasize moral and religious development, yet their structured environments often present unique challenges. Studies have shown that santri (students) struggle with stressors including heavy academic and religious demands, social adaptation, and cultural differences (Nabilah, Arifin, & Tarsono, 2022; Misbahudin & Munawaroh, 2024; Alfarisi, Mulyanto, & Waspodo, 2022). For example, Ayu, Sundari, and Rahmawati (2024) found that 83.4% of pesantren students reported mild-to-moderate stress, significantly associated with adaptability issues.To address these challenges, expressive writing has emerged as a promising psychological intervention. Originally developed by Pennebaker, expressive writing enables individuals to articulate their deepest emotions and thoughts, promoting both emotional catharsis and cognitive restructuring (Pennebaker & Seagal, 1999). Empirical evidence supports its benefits, including improved emotional regulation, reduced stress, enhanced resilience, and better physical health (Baikie & Wilhelm, 2005; Kirk, Schutte, & Hine, 2011; Travagin, Margola, & Revenson, 2015). Structured in four stages-recognition, examination, reflection, and application-expressive writing facilitates meaning-making and self-clarity (Oentarto, 2021).This study investigates the effectiveness of expressive writing in enhancing psychological well-being among students in an Islamic boarding school. The research tested two hypotheses: (1) there would be a significant difference between pre-test and post-test scores in the experimental group, and (2) there would be a significant difference in post-test scores between the experimental and control groups.